Flyway population delineation in Taiga Bean Geese Anser fabalis fabalis revealed by multi‐element feather stable isotope analysis. (31st October 2016) - Fox, Anthony D.; Hobson, Keith A.; de Jong, Adriaan; Kardynal, Kevin J.; Koehler, Geoff; Heinicke, Thomas
Abstract : Fundamental to effective management of migratory waterbird populations is an understanding of their flyway delineation. Taiga Bean Geese Anser fabalis fabalis wintering in NW Denmark, Scotland and England are considered to originate from northern and central Sweden, southern and central Norway ('Western flyway'), those wintering in southern Sweden, NE and southern Denmark are considered to originate from northern Fennoscandia and western Russia ('Central flyway'), and those wintering in eastern Germany and Poland (which show far less favourable conservation status) are thought to come from western Siberia ('Eastern 1 flyway'), although evidence to demonstrate this has largely been lacking. Evidence for different natal and moult origins of Taiga Bean Geese was investigated using stable isotope analyses of feathers of four elements ( δ 2 H, δ 13 C, δ 15 N and δ 34 S). There were significant differences in isotopic composition of feathers from Swedish (Central) and German (Eastern 1) wintering populations and those moulting in Sweden in late summer (Western), which validated the three proposed major management flyway units above. The strong continental gradient in the stable hydrogen isotope ratios in precipitation ( δ 2 Hp ) across the region was used to assign wintering birds geospatially to natal and moulting origin, indicating separate natal and moulting areas for German ( n = 37, from western Siberia) and Swedish ( n = 20, Fennoscandia and more western Russia) wintering birds. These results confirm the largely discrete nature of these three flyways and contribute significantly to our ability to deliver effective targeted and appropriate research, monitoring and management actions throughout the ranges of these flyways.